ANALISIS PEMBIAYAAN MUSYARAKAH DI KSPPS BMT HALAQOH PADA SEKTOR PERTANIAN DI DESA JOGOROGO - Rinata, Selvia Luxi (Commodity : Jurnal Perbankan dan Keuangan Islam, 2024)
This research, titled "Analysis of Musyarakah Financing at KSPPS BMT Halaqoh Jogorogo in the Agricultural Sector in Jogorogo Village," is a descriptive qualitative study that aims to explore how Musyarakah financing is applied to support agricultural costs. The research employs a qualitative approach using data collection techniques such as interviews and literature reviews, including documents, books, and brochures. Primary data serves as the main source, while secondary data supports the primary findings. The results indicate that the procedures, collateral requirements, and provisions for Musyarakah financing at KSPPS BMT Halaqoh comply with Islamic principles. All components of the Musyarakah contract, including the offer and acceptance (ijab qabul), capital contribution, involved parties, as well as profit-sharing and responsibilities, are properly implemented. In the event of crop failure, the institution does not demand a share of the profit but replaces it with infaq (voluntary charity), while loan installments remain due as per the agreement. The financing system is free from elements of riba (usury) as it aligns with the fatwas issued by Indonesia's National Sharia Council (DSN-MUI). Consequently, this financing model provides convenience and peace of mind to farmers, enabling them to cultivate their land productively and improve their welfare.